Legal responsibility in the mechanism of legal regulation - Свиридюк, Наталія Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In this article an author investigates the questions of the functional role of legal responsibility in the context of the mechanism of legal regulation.